(untitled) (Research, Society and Development, 2022)
In this article we observe and analyze the promotion and prevention actions carried out by Community Health Agents (CHA) in the first Home Visit to the newborn. Which is ensured by the Ministry of Health and must be carried out on the fifth day of the newborn’s life, aiming to prevent all the risks that the individual is exposed to at this stage. Aiming to know which health promotion and prevention actions are addressed by the ACS during the first home visit to the newborn. The research was carried out in an observational, descriptive way, with a qualitative approach, through Bardin’s theory, at the Sacramenta II Family Health Unit, in the Sacramenta neighborhood, in the municipality of Belém-PA. The survey showed that more than half of the professionals had little knowledge of their skills and how the visit should take place, thus demonstrating a gap in the health service.